2015
DOI: 10.1002/ldr.2395
|View full text |Cite
|
Sign up to set email alerts
|

Fire‐Free Fallow Management by Mechanized Chopping of Biomass for Sustainable Agriculture in Eastern Amazon: Effects on Soil Compactness, Porosity, and Water Retention and Availability

Abstract: Many Amazon soils are naturally fragile and develop under intense rainfall and high temperature climate. Soil structural quality is improvable through vegetation management systems providing abundant soil mulch and little soil disturbance. We tested the effect of the chopping‐and‐mulching systems of secondary forest‐vegetation on selected soil physical properties of a sandy Oxisol, located in the eastern Brazilian Amazon. The treatments consisted of two fallow forest‐vegetation, namely, chop‐and‐mulch of secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 61 publications
1
18
0
1
Order By: Relevance
“…Chop-and-mulch, a fire-free technique for land preparation (Denich et al, 2004), conserves nutrients, improves soil quality, and reduces carbon dioxide-equivalent emissions from the soil to the atmosphere in comparison to slash-and-burn, as shown by studies conducted in eastern Amazonia (Sommer et al, 2004;Davidson et al, 2008;Comte et al, 2012;Reichert et al, 2015Reichert et al, , 2016). However, chop-and-mulch has not always increased soil carbon stocks (Perrin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Chop-and-mulch, a fire-free technique for land preparation (Denich et al, 2004), conserves nutrients, improves soil quality, and reduces carbon dioxide-equivalent emissions from the soil to the atmosphere in comparison to slash-and-burn, as shown by studies conducted in eastern Amazonia (Sommer et al, 2004;Davidson et al, 2008;Comte et al, 2012;Reichert et al, 2015Reichert et al, , 2016). However, chop-and-mulch has not always increased soil carbon stocks (Perrin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In some areas, farmers intercrop annual agricultural species and secondary forest after slashing and burning forested areas. Such practice is based on indigenous agricultural system, which is characterized by long fallow periods after a short cultivation period of 1-3 years (Davidson et al, 2008;Comte et al, 2012;Reichert et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…(), which used principal component analysis to identify the differences on soil microbial community structure induced by burning, and Reichert et al . (), which applied the analysis of variance (ANOVA) in the evaluation of Amazon soil properties after fires.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of change in land use and occupation in the dynamics of fires and burnings around the world is investigated from various aspects (Reichert et al, 2015). Cerdà & Lasanta (2005) observed that fire in the Central Spanish Pyrenees occurs in controlled areas.…”
Section: Introductionmentioning
confidence: 99%